2022
DOI: 10.15561/26649837.2022.0402
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 8 weeks plyometric exercise on physical and motoric features of mental disabled

Abstract: Background and Study Aim. Physical activity for disabled people is a long-debated issue. The number of studies examining the effects of alternative exercise programs on the physical and motor outcomes of people with intellectual disabilities is limited. For this reason, the purpose of this study is to investigate the effects of 8-week plyometric exercises on some physical and motor characteristics of mentally retarded people. Material and Methods. The method of this study is the experimental method, one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Previous research has shown similar benefits of physical activity programs for children with ID. For instance, study by Kurtoğlu et al (2022) explored the effects of an 8-week plyometric exercise program on physical and motor skills in 24 students aged 11-17 with moderate to mild intellectual disabilities. Participants completed the exercises three times a week.…”
Section: Social Interactionmentioning
confidence: 99%
“…Previous research has shown similar benefits of physical activity programs for children with ID. For instance, study by Kurtoğlu et al (2022) explored the effects of an 8-week plyometric exercise program on physical and motor skills in 24 students aged 11-17 with moderate to mild intellectual disabilities. Participants completed the exercises three times a week.…”
Section: Social Interactionmentioning
confidence: 99%
“…The instrument for measuring mental health was the DASS-21 with three subscales: (1) depression related to hopeless, passivity, low-selfesteem, dysphoria and anhedonia, (2) anxiety related to feeling of situational anxiety and autonomic arousal and (3) stress related to nervous arousal, relaxing, irritable, and upset [23]. According to Ghani, Zainuddin, Ibrahim, Hashim & Van [51], the depression subscale consisted 3, 5, 10, 13, 16, 17 and 21 question items. Depression with normal levels (0-9), mild (10)(11)(12), moderate (13)(14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27) and very severe (28-42).…”
Section: Mental Healthmentioning
confidence: 99%